Research on the quality supervision strategy of drugs sold on the internet under the MAH system - Wen, Zongliang; Chen, Jialin; Zhou, Li; Bai, Long; Wu, Shenqin; Zhao, Yun; Fang, Jinhua (Frontiers in Public Health, 2025)
BackgroundIn recent years, purchasing medications online has become increasingly popular. However, occasional quality issues have arisen with drugs bought online. As a result, we need effective quality monitoring of medicines sold online. To address this issues, several countries have begun to implement the Marketing Authorization Holder (MAH) system to enhance drug quality control.MethodsConsequently, this paper develops a four-party evolutionary game model that includes the government, holder, agent seller and third-party platform in pharmaceutical online sales, and use Matlab 2022b to carry out numerical simulation, and to compare and analyze the influence of different factors on the strategy selection of the main body of the game by changing parameters. This paper is based on the multi-party game perspective, constructed a hierarchical model, thereby better exploring the mechanism of drug quality regulation in the context of drug online sales under the MAH system.ResultsFindings suggest that reducing operational costs motivates agent sellers to adopt stable, honest strategies. Increased government penalties expedite the adoption of positive strategies by sellers, holders, and third-party platforms. Enhanced penalties from holders and platforms for defaults effectively regulate seller behavior. Additionally, reputation rewards or losses incentivize sellers to adopt honest practices, with consumer and sellers' reputations influencing the likelihood of comprehensive third-party platform reviews.ConclusionsIn summary, policy makers should improve the regulatory mechanism, establish a fair system of rewards and penalties, develop a compensation mechanism for information sharing, deregulate prices and enhancing feedback channels.